Plurality or convergence in sustainability reporting standards? - Nadia Albu; Cătălin Nicolae Albu; Mădălina Dumitru; Valentin Florentin Dumitru (Amfiteatru Economic)
Over the last years an increasing number of companies issued Corporate Social Responsibility (CSR) or Sustainability Reports to complement their traditional financial reporting. Companies use various sustainability reporting standards or develop their own reporting frameworks starting from the existing ones. This variation of practices pointed out by empirical research raises questions about the quality and comparability of sustainability reporting, its role in the sustainable development, and also about the suitability of accepting the plurality of reporting frameworks or the need for convergence. This study aims to investigate the issues of plurality and convergence in sustainability reporting standards, by mobilizing the discourses on regulation and the case of a group of companies in the IT industry in order to shed some light on the current challenges in this area. We frame a discussion on the opportunities and pitfalls of convergence in sustainability reporting regulations and contribute to a better understanding of this issue by academics, preparers, users and standard setters